Pathological internet use among adolescents: comparing gamers and non-gamers - Strittmatter, Esther; Kaess, Michael; Parzer, Peter; Fischer-Waldschmidt, Gloria; Brunner, Romuald (Psychiatry research, 2015)
“Internet gaming disorder” was recently included in Section 3 of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5). Non-gaming Internet activities were not considered because of a lack of evidence. This study examined whether gamers differ from non-gamers with respect to their psychological well-being among students who show pathological Internet use (PIU). This cross-sectional study was conducted within the project “Working in Europe to Stop Truancy Among Youth (WE-STAY)”. A total of 8807 European representative students from randomly selected schools were included. The Young Diagnostic Questionnaire was applied to assess PIU, and students with this condition were divided into gamers (PIU-G) and non-gamers (PIU-NG). Overall, 3.62% and 3.11% of the students were classified as having PIU-G and PIU-NG, respectively. A multinomial logistic regression revealed that students with PIU-G and those with PIU-NG showed similarly increased risks for emotional symptoms, conduct disorder, hyperactivity/inattention, self-injurious behaviors, and suicidal ideation and behaviors. Students with PIU-G were more likely to be male and have a higher risk for peer problems than those with PIU-NG. Students with PIU-NG had a higher risk of depression than those with PIU-G. The significant psychological impairment of PIU-NG suggests that it should be considered in future diagnostic criteria.
Gesehen am 22.02.2017